A highly spatially resolved GIS-based model to assess the isoprenoid emissions from key Italian ecosystems - Pacheco, Claudia Kemper; Fares, Silvano; Ciccioli, Paolo (Atmospheric Environment, 2014)
The amount of Biogenic Volatile Organic Compounds (BVOC) emitted from terrestrial vegetation is of great importance in atmospheric reactivity, particularly for ozone-forming reactions and as condensation nuclei in aerosol formation and growth. This work presents a detailed inventory of isoprenoid emissions from vegetation in Italy using an original approach which combines state of the art models to estimate the species-specific isoprenoid emissions and a Geographic Information System (GIS) where emissions are spatially represented. Isoprenoid species and basal emission factors were obtained by combining results from laboratory experiments with those published in literature. For the first time, our investigation was not only restricted to isoprene and total monoterpenes, but our goal was to provide maps of isoprene and individual monoterpenes at a high-spatial (∼1 km2) and temporal resolution (daily runs, monthly trends in emissions are discussed in the text). Another novelty in our research was the inclusion of the effects of phenology on plant emissions. Our results show that: a) isoprene, a-pinene, sabinene and b-pinene are the most important compounds emitted from vegetation in Italy; b) annual biogenic isoprene and monoterpene fluxes for the year 2006 were ∼31.30 Gg and ∼37.70 Gg, respectively; and c) Q. pubescens+Q. petrea+Q. robur, Q. ilex, Q. suber and Fagus sylvatica are the principal isoprenoid emitting species in the country. The high spatial and temporal resolution, combined with the species-specific emission output, makes the model particularly suitable for assessing local budgets, and for modelling photochemical pollution in Italy.
Keywords: BVOC inventory; isoprene; Isoprenoids; Italian forests; Monoterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes

Intra- and inter-annual variability of VOC emissions from natural and semi-natural vegetation in Europe and neighbouring countries - Steinbrecher, Rainer; Smiatek, Gerhard; Köble, Renate; Seufert, Günther; Theloke, Jochen; Hauff, Karin; Ciccioli, Paolo; Vautard, Robert; Curci, Gabriele (Atmospheric Environment, 2009)
Biogenic VOC emission estimates from the earth’s surface are crucial input parameters in air quality models. Knowledge accumulated in the last years about BVOC source distributions and chemical compound species emission proﬁles in Europe as well as the demand of air quality modellers for a ﬁner resolution in space and time of BVOC estimates have led to the set-up of new emission modelling systems. An updated fast BVOC emission modelling platform explicitly considering the seasonality of emission potentials and leaf temperature gradients in forest canopies by the semi-empirical emission module (seBVOC) will be proposed and used for estimating hourly values of chemical compound-speciﬁc emissions in Europe (33–68 north; 10 west to 40 east) in the years 1997, 2000, 2001, and 2003. Spatial resolution will be 10 km by 10 km. The database used contains latest land and forest distributions, updated foliar biomass densities, leaf area indices (LAI), and plant as well as chemical compound-speciﬁc emission potentials, if available. Meteorological input parameters for the respective years will be generated using the non-hydrostatic meteorological model MM5. Highest BVOC emissions occur in daytime hours around noon from the end of May to mid-August in the Mediterranean area and from the mid of June to the end of July in the boreal forests. Comparison of 3 BVOC model approaches will reveal that for July 2003, the European isoprene and monoterpene totals range from 1124 Gg to 1446 Gg and from 338 Gg to 1112 Gg, respectively. Small-scale deviations may be as high as 0.6 Mg km2 for July 2003, reﬂecting the current uncertainty range for BVOC estimates. Key sources of errors in inventories are still insufﬁciently detailed land use data for some areas and lacking chemically speciated plantspeciﬁc emission potentials in particular in boreal, south-eastern, and northern African landscapes. The hourly emissions of isoprene, speciated terpenes, and oxyVOC have been made available by the NatAir database.
Keywords: BVOC; Emission modelling; Inventory; Isoprenoids; oxyVOC; Sequiterpenes